Study Of Knowledge, Attitude & Practice Regarding the Various Methods of Contraception in A Rural Setup of Hoskote - Yogendra V; Ahmed, Shuaib; Jaweriya, Sana; Mullick, Sagorika (National Journal of Community Medicine, 2012)
Background: Contraception is as old as mankind.In view of increasing population there’s need for awareness regarding the use of various contraceptive methods. Aims and Objectives: To assess the Knowledge, Attitude & Practice regarding the various contraceptive methods in a rural setup of Hoskote. Materials & Methods: A cross sectional study was carried out at MVJ, UHC & PHC of Hoskote Taluk on OPD basis. Data was collected by a pre-designed questionnaire at the OPD. Statistical analysis was done using SPSS software. People were simultaneously educated regarding the various contraceptive methods. Results: Total sample size was 150 of which 75 were males and 75 females. Knowledge about contraceptives was seen more in males (93.3%) when compared to females (72%). 95.2% of gradates had knowledge regarding the methods of contraception. This suggests that the knowledge about contraception is better perceived and understood among the literate group. Most common method of contraceptive practiced was barrier methods (40%), followed by sterilization procedure (20%), IUCD (18.67%), OCP (12%), coitus interruptus (8.67%) and emergency contraception (0.67%). Conclusion: There has been a considerable improvement among the people even in rural setup regarding the contraceptive use, but there still exists lack of awareness and knowledge regarding the use of contraceptive methods in some small groups of people. IEC activities have to be increased especially for females of this rural setup.